A Canadian algorithm for upper gastrointestinal cancer management - Lemay, Frédéric; Sandhu, Amindeep S.; Stein, Barry D.; Goodwin, Rachel (Frontiers in Oncology, 2025)
Recent advances in immunotherapy have changed the treatment landscape for cancers of the upper gastrointestinal (GI) system. Immune checkpoint inhibitors can lead to better survival and improved quality of life for affected individuals. Adopting new treatment strategies in real-world practice can be challenging, and algorithms that are easy to implement in Canadian oncology practices would benefit clinicians and patients. In this study, we present expert opinion on best practices for upper GI cancer management, including a new algorithm that integrates the latest evidence for screening, workup, diagnosis, treatment, and survivorship. The algorithm is based on a novel approach comprising a case-based, accredited educational program with asynchronous discussion among clinicians practicing across Canada, with the input of expert medical oncologists and gastroenterologists. A needs assessment was employed to determine current areas of educational need in the field of upper GI cancers, and a patient representative provided insights into patient concerns and priorities. The best practices described here include seeking patient input throughout treatment, integrating immune checkpoint inhibitors into systemic therapy for both localized and advanced disease, and providing comprehensive supportive care throughout the treatment and survivorship journey.